Storm-induced changes in environmental conditions are correlated with shifts in temperate reef fish abundance and diversity - Munks, L.; Harvey, Euan; Saunders, Ben (Elsevier, 2015)
We studied the effects of regularly occurring non-destructive storm events on a temperate Australian reef fish assemblage. We collected 78 remote underwater stereo-video samples during four storms. The relative abundance and species richness of fishes were compared to environmental data (significant wave height, water motion, temperature, light intensity and mean surface level pressure) collected during each storm. As wave height and water motion increased, there was a general decline in abundance of fishes and species richness within the assemblage. The variation in the total number of individual fishes was best explained by a combination of water motion, mean surface level pressure, and temperature. Species richness decreased at the height of the storms, and was best explained by significant wave height and mean surface level pressure. Certain fish species were observed to be highly sensitive to fluctuations in different environmental variables, while others proved more resilient to the changing conditions. Sensitive species such as Austrolabrus maculatus disappeared from the recorded assemblage when wave height reached ~ 3 m. In contrast, more resilient species such as Parma mccullochi persisted until the occurrence of more severe conditions (wave height > 5 m).In addition to wave height and water motion, temperature, light intensity and mean surface level pressure all contribute to models explaining variation in the abundance of fish species during these storm events. We suggest that environmental changes during storm events have an influence on the behaviour of fishes depending on their morphological and physiological characteristics, and that sensitive species may migrate from the area or seek refuge in the reef substrate to weather the storm. Our results suggest that it may be important to consider meteorological conditions when conducting fish surveys, and further work should examine the susceptibility of different species to rapid changes in environmental conditions.